Navigating job satisfaction in family firms during crisis - Ibañez, Maria Jose; Andrade-Valbuena, Nelson A.; Llanos-Contreras, Orlando (Frontiers in Psychology, 2024)
Occupational health is one of the aspects significantly affected during crisis periods. It is essential to learn about the factors that improve organizational capacity in coping with such shocks. This study investigates how the working environment of a family business influences job satisfaction during crises. Conducting a survey with 516 employees at the peak of the pandemic, the research utilizes Structural Equation Analysis, revealing that family business environments can mitigate burnout, enhance affective commitment, and consequently, boost job satisfaction. The study highlights the need to manage burnout and utilize resources, such as employee commitment, for family firms to sustain job satisfaction amidst disruptions. It deepens the comprehension of family businesses' crisis response, emphasizing the significance of human resource commitment and management. The investigation illuminates the dynamic interplay between the work environment, employee well-being, and organizational resilience, providing valuable insights for both theoretical understanding and practical application.